Parent‐adolescent influences on everyday dietary practices: Perceptions of adolescent females with obesity and their mothers. Issue 4 (17th January 2017) - Winkler, Megan R.; Moore, Elizabeth D.; Bennett, Gary G.; Armstrong, Sarah C.; Brandon, Debra H.
Abstract: Parents demonstrate an important influence on adolescent obesity and dietary behavior; yet, family‐based obesity interventions continue to exhibit limited success among adolescents. To further inform family‐based approaches for adolescent obesity treatment, we examined the perceptions of adolescent females with obesity and their mothers of the influences experienced within the parent‐adolescent relationship that affect everyday dietary practices. We conducted six focus group interviews (three adolescent female and three mother) among 15 adolescent (12–17 years old) females with obesity and 12 of their mothers. Content analysis techniques were used to analyze the transcribed interviews. Adolescent females with obesity discussed a diverse set of parental influences (controlling, supporting and cultivating, overlooking and tempting, acquiescing, providing, attending, and not providing and avoiding) on their daily dietary practices. Among mother focus groups, mothers discussed specific intentional and unintentional types of influences from children that affected the food and drink they consumed, prepared, and acquired. Findings provide a fuller view of the varied social influences on everyday dietary practices within the parent‐adolescent relationship. They indicate the importance of examining both parent‐to‐child and child‐to‐parent influences and begin to illuminate the value of attending to the social circumstances surrounding dietary behaviors to strengthen family‐based obesity treatment approaches.